Improving Students’ Speaking Skill by Using Scripted Role Play at Class XI MIPA-2 Students of SMA Negeri 12 Makassar - Maria Fatima Jaina; Sukmawati; Suharti Siradjuddin (CV. Eureka Murakabi Abadi, 2022)
Speaking English fluently, precisely and structured is a skill that is highly expected from students. However, in reality there are still many students who find difficulties to apply it simultaneously in English. So, it takes practice every day to hone students' speaking skills. For this reason, the writer wants to improve students' English skills using an appropriate learning method, namely Scripted Role Play. This research was conducted in two cycles. It consists of: planning, action, observation and reflection. Each cycle consists of four meetings, three meetings for presenting the material and the fourth meeting was speaking test. The data of this research were obtained using quantitative data (oral tests) as the main data and qualitative data (field notes and documentation) as supporting data. The results of research showed that students experienced improvement in speaking English. This is evidenced by the average score obtained by students in thefirst cycle test to the second cycle test. In the first cycle test the average score of students was 69.44 where there are 16 (44.44%) students who passed the minimum completeness criteria, and the average of the second cycle was 80.13 where there were 31 students (86.11) students who passed the minimum completeness criteria. This shows that through the Scripted Role Play teaching method the students have improved in speaking English.